When to change treatment of acute invasive aspergillosis: an expert viewpoint. (11th September 2021) - Slavin, Monica A; Chen, Yee-Chun; Cordonnier, Catherine; Cornely, Oliver A; Cuenca-Estrella, Manuel; Donnelly, J Peter; Groll, Andreas H; Lortholary, Olivier; Marty, Francisco M; Nucci, Marcio; Rex, John H; Rijnders, Bart J A; et al.
Abstract: Invasive aspergillosis (IA) is an acute infection affecting patients who are immunocompromised, as a result of receiving chemotherapy for malignancy, or immunosuppressant agents for transplantation or autoimmune disease. Whilst criteria exist to define the probability of infection for clinical trials, there is little evidence in the literature or clinical guidelines on when to change antifungal treatment in patients who are receiving prophylaxis or treatment for IA. To try and address this significant gap, an advisory board of experts was convened to develop criteria for the management of IA for use in designing clinical trials, which could also be used in clinical practice. For primary treatment failure, a change in antifungal therapy should be made: (i) when mycological susceptibility testing identifies an organism from a confirmed site of infection, which is resistant to the antifungal given for primary therapy, or a resistance mutation is identified by molecular testing; (ii) at, or after, 8 days of primary antifungal treatment if there is increasing serum galactomannan, or galactomannan positivity in serum, or bronchoalveolar lavage fluid when the antigen was previously undetectable, or there is sudden clinical deterioration, or a new clearly distinct site of infection is detected; and (iii) at, or after, 15 days of primary antifungal treatment if the patient is clinically stable but with ≥2 serum galactomannan measurements persistently elevated compared with baseline or increasing, or if the original lesions on CT or other imaging, show progression by >25% in size in the context of no apparent change in immune status.